3-Arylcoumarin inhibits vascular calcification by inhibiting the generation of AGEs and anti-oxidative stress - YuFei Li; Yinbo Pan; Liying Wang; Xiaojing Wang; Haiping Chu; Yan Li; Jie Sun; Yanling Mu (Taylor & Francis Group, 2022)
Objective This work aims to screen drugs for preventing and treating vascular calcification. Method: We screened a series of 3-arylcoumarins for the detection of vascular calcification-associated factors using human aortic vascular smooth muscle cells.Results We found that compounds 14 and 32 significantly inhibited alkaline phosphatase (ALP) activity similar to aminoguanidine hydrochloride (AGH) in a cellular model of AGEs-induced calcification. We also found that compounds 14 and 32 could significantly decrease the levels of factors such as AGEs, intracellular calcium ions, and total ROS in the calcified cell model. Further study indicates that compound 14 could significantly inhibit the expression of P-ERK1/2, PKC, NF-κB, RAGE and OPN proteins and increased the expression of SM22-α and PPAR-γ proteins in the calcified cells.Conclusion We speculate that compound 14 inhibits vascular calcification by inhibiting oxidative stress and inhibiting AGEs production, suggesting that 3-arylcoumarin derivatives are potential candidates for the treatment of vascular calcification.